A technology foresight on electric motorcycle adoption in the Philippines through scenario building - Santos, Alvin C.; Imbang, Glen A. (Quezon City University of the Philippines Diliman, 2015)
This study entitled "A Technology Foresight on Electric Motorcycle Adoption in the Philippines" aims to determine the plausible scenarios for adoption of electric vehicles (EVs), particularly electric motorcycles, in the Philippines by 2020.

Scenario building was used as technology foresight technique. Environmental analysis covering political, economic, sociological, technological, environmental, and legal (PESTEL) aspects supplemented the discussion. PESTEL analysis was used as bases for identification of key predictable variables and critical uncertainties. In turn, both key predictable variables and critical uncertainties was clustered and ranked to establish the key driving forces that may affect the adoption of electric motorcycles in the Philippines. Scenario logic were drawn out from the key driving forces. Plausible scenarios were developed and assessed through SWOT analysis. Finally, the developed scenarios were assessed in terms of its implications to strategic planning for the EV industry stakeholders in the Philippines.

Scenario Building exercise, discussions and analyses, led to the following conclusions : 1. The Philippines may potentially become the EV hub of Asia; 2. Achieving eVAP's target of a million EVs by 2020 would also translate to EVs successfully penetrating the "early majority" adopters; and 3. EVs will not completely replace traditional ICE-based motorcycles, but will become a viable alternative mode of transportation.

The following recommendations can also be drawn : 1. Alignment of Philippine EV industry targets with eVAP's one million EVs by 2020 in order for EVs to become a lucrative business venture. 2. Formation of a consortium for EV technology acquisition to achieve technology independence; and 3. Expand by exporting EVs to foreign markets.
In partial fulfillment of the requirements of TM 299
Thesis
Keywords: Technological forecasting; Electric motorcycles -- Philippines; Business planning; Scenario building